Computational Intelligence for Supply Chains - Vasant, Pandian 1961-; Weber, Gerhard-Wilhelm 1960-; Munapo, Elias; Banik, Anirban (De Gruyter, 2023)
This book provides details on current approaches of artificial intelligence, focusing on supply chains design and management across strategic industries. Topics such as intelligent algorithmic enhancements and smart performance measurement approaches are discussed, and insights into the implementation of sustainable computational intelligence strategies to current problems are given.
Erscheint ca Februar 2024
Keywords: Industrie 4.0; Künstliche Intelligenz; Supply Chain Management; Algorithmus